Evaluation of the Sustainable Aspects In Housing Sector To Overcome Housing Stress In Northern Iraq - RAHEL MOHAMMED AMIN; SALAR SALAH MUHY AL-DIN (Journal of Contemporary Urban Affairs, 2019)
Northern Iraq as part of Iraq, has been witnessed a great population increment last few decades. However, housing stress in Northern Iraq has risen due to that. Environmental, economic and social sustainability became crucial in the movement towards a more effective built environment and community nowadays. This research seeks to evaluate the presence of sustainability aspects (environmental, economic, and social) in the housing sector, which makes them acquired and affordable for low-income earners in Northern Iraq. Housing projects as case studies were investigated in Erbil, the capital of Northern Iraq. The research examined, the presence of sustainability aspects. Field observations checklist has been prepared based on the theoretical analysis through literature review and applied to collect data on the case studies. The results demonstrated that applying the aspects of sustainability for the buildings is weak and not clearly familiar in Northern Iraq. The study concluded that the housing projects focusing on the case study not sustainable. The findings show that the application of sustainable principles in the housing projects in Northern Iraq is very weak. It is highly recommended to achieve sustainability, because it is a significant way to produce acquired and affordable housing and overcome the housing problems, socially, environmentally and economically. The recommendations have been suggested to formulate new ways of implementing sustainable principles in the housing sector to overcome housing stress in Northern Iraq.